(untitled) (Swiss Medical Weekly, 2025)
INTRODUCTION: The Swiss Society of Paediatrics currently recommends the growth references of the World Health Organization (WHO), while the Paediatric Endocrinology Centre Zurich (PEZZ) has proposed alternative growth references. Specialists and researchers also use International Obesity Task Force (IOTF) references to define overweight and obesity. We investigated the fit of anthropometric measurements from schoolchildren in the canton of Zurich to these three growth references and assessed the prevalence of overweight, obesity and short stature across the three references. METHODS: We analysed data from 3755 children aged 6–17 years in the cross-sectional LuftiBus in the School (LUIS) study, collected in the period 2013–2016 in the canton of Zurich. We calculated z-scores of height, weight and body mass index (BMI) based on WHO, PEZZ and IOTF references. We compared the mean and distribution of z-scores to the expected standard normal distribution using the Anderson-Darling test. We classified overweight, obesity and severe obesity based on cutoff values given by the three references. We defined short stature as <3rd percentile of height for age. RESULTS: The mean z-scores in LUIS were 0.56 for height, 0.28 for weight and 0.06 for BMI based on WHO references; 0.15 for height, 0.06 for weight and −0.01 for BMI based on PEZZ references; and 0.19 for BMI based on IOTF references. The Anderson-Darling test showed that children in LUIS fit worse to WHO and IOTF than to PEZZ references. The WHO classified fewer children as overweight than PEZZ and IOTF references (WHO: 8%; PEZZ: 15%; IOTF: 13%) but more children as obese or severely obese (6%; 4%; 3%). The WHO defined fewer children as being of short stature than PEZZ references (1% vs 3%). CONCLUSIONS: Our findings suggest that anthropometric data of schoolchildren in Zurich (LUIS) differ notably from WHO and IOTF references potentially leading to misclassification of overweight, obesity and short stature. Thus it would be timely to develop new nationally representative growth references for Switzerland.